MONITORING FUNDAMENTAL REACTIONS AT NIASS SURFACES BY SYNCHROTRON RADIATION X-RAY PHOTOELECTRON SPECTROSCOPY: AS AND S AIR OXIDATION BY CONSECUTIVE REACTION SCHEMES - Nesbitt H.W.; Schaufusz A.; Sciani M.; Hchst H.; Bancroft G.M.; Szargan R. (My University, 2003)
Synchrotron X-ray photoelectron As 3d and S 2p spectra of gersdorffite reveal that the surface monolayer includes two types of surface anionic species, As-S dimers and As-S multimers (probably tetramers), the latter being the product of a polymeric surface reaction, implying that the surface undergoes some reconstruction. Monomeric states of S and As may also be present at the surface. Formation of the tetramers is energetically favored in that two dangling bonds are eliminated with formation of each tetrameric surface species. Reaction of air with NiAsS is initiated by oxidation of As surface species, which is rapid compared with oxidation of sulfur species. Oxidation of both As and S proceeds by production of numerous intermediate reaction products in which As and S display intermediate oxidation states. The abundances of sulfur and arsenic intermediate oxidation products initially increase, achieve maxima, then decrease as the final oxidation products (arsenate and sulfate) accumulate. These trends in abundance suggest that air oxidation of As and S proceeds by consecutive reaction schemes and that the elementary reactions of these schemes involve transfer of only one electron per reaction step. Sulfur is the most electronegative of the surface atoms, and the associated dangling bond likely contains a lone pair of electrons, thus imparting diamagnetic character to the surface atom. Arsenic surface atoms should have greater tendency toward paramagnetic character, and this may explain the greater rate of As oxidation during exposure of gersdorffite to the atmosphere. Air-oxidized fractured surfaces and polished surfaces of NiAsS rapidly develop an overlayer containing primarily As-bearing species in both reduced and oxidized forms. The oxidized overlayer is, by contrast, virtually devoid of S and Ni, demonstrating preferential diffusion of As from the bulk into the overlayer.